A study on Sentence-Final Particle Words of the Tong Group in the XianLuoGuanYiYu - Pan, Lei; Keawsuwan, Chatuwit (Language and Linguistics, 2021)
This study aims to analyse phono-semantic compounds of the Tong (通, tōng) group as sentence-final compounds according to the principles of XianLuoGuanYiYu (暹羅館譯語, xiānluóguǎn yìyǔ) in Historical Chinese phonology (音韻學, yīnyùn xué), using a comparative approach to Siamese language and modern-day Thai language. The study also analyses the sound transcriptions in comparison to the Siamese language sound system and sound descriptions as described in the HongWuZhengYun (洪武正韻, hóngwǔ zhèngyùn) alphabetical index in order to identify the origins of the Chinese variations used at the time. It also attempts to understand more about how sounds are transcribed between languages as well as how the languages have changed throughout the years. The study reports that: 1) the โ-ะ โ-อุ และ อู vowels with the letter ม in the coda position causes inflection to the vowel sound. The inflection causes the vowel sounds to become /i/ and the /ง/ final sound to become the /ม/ sound in the coda position. All of these Chinese characters that this phenomenon applies to belong to Level 3, 2) the โ-ะ โ- อุ และ อู vowels with alphabet ง in the coda position; the phenomenon shortens the /i/ vowel sound while the /ง/ retains its presence. All of these Chinese characters also belong to Level 3, 3) the Chinese characters with sounds similar to the Siamese sounds used at the time belong to Level 1, 4) vowels with letters /น/ or /n/ in Chinese and vowels with letters /ม/ or /m/ in the coda position only has one word that is assumed to be the result of ‘anticipatory assimilation’.